Proceedings of the 1st International Discussion Meeting on Superionic Conductor Physics : Kyoto, Japan, 10-14 September 2003 - Kawamura, Junichi (World Scientific, 2007)
The book presents basic studies on ion transport properties of ionic conductive solid. It describes research on theory, modeling, simulation, crystalline structure, nuclear magnetic resonance, electric conduction, optical properties, and thermal measurement in this field. Superionic conductors are highly promising functional materials. As a stepping stone in the development of new superionic conductors that can be utilized as functinal materials efforts to reevaluate solid-interior diffusion and conduction phenomena of ions and molecules in a superionic conductor on the basis of basic physical.